PEMANTAUAN KUALITAS MIKROBIOLOGIS PADA PERMUKAAN MEJA KERJA PENGUJIAN LABORATORIUM MIKROBIOLOGI SEBELUM DI DESINFEKSI BERDASARKAN TOTAL PLATE COUNT DENGAN METODE SWAB - Farah Syifa Zayyanna, Salma; Fitria Firdhausi, Nirmala (Jurnal Biogenerasi, 2025)
Microbiology laboratory environmental monitoring is an activity that must be considered to ensure that there is no contamination either directly or cross-contamination. Environmental monitoring can be carried out using the swab method in accordance with SNI 2332.3: 2015. This study shows that the sample preparation room has a high contamination rate exceeding the limits specified in SNI 2332.3: 2015. Contamination in the sample preparation room has a figure of 1.4 x 104 cfu / 100 cm2. Inoculation room 2 (LAF) has the lowest contamination rate, this is influenced by the pressure around the room which is useful for reducing contamination. This monitoring must be carried out periodically to ensure that the environmental conditions are clean and sterile, thereby reducing the possibility of contamination of products and test results.